EU enlargement and migration: Assessing the macroeocnomic impacts - Ray Barrell; John Fitz Gerald; Rebecca Riley (The Economic and Social Research Institute (ESRI), 2007)
This paper considers the macroeconomic effects of the migration that followed the enlargement of the EU in May 2004. At that time the EU was expanded to include 10 New Member States (NMS) predominantly from Central and Eastern Europe. In the wake of accession the number of workers migrating to the EU-15 from the poorest of the NMS increased significantly. In part the result of the liberal immigration policies adopted, and restrictive policies adopted elsewhere, Ireland and the UK have become popular destination countries for NMS workers. Here we illustrate the potential macroeconomic consequences of these migration flows across Europe, highlighting the impacts in both the receiving and sending countries.
Keywords: E22; E24; E27; F22; J61; 330; EU enlargement; New Member States; migration; EU-Erweiterung; Internationale Wanderung; Makroökonomischer Einfluss; Prognose; EU-Staaten (Osteuropa); EU-Staaten